The influence of aluminum nanoparticles on the laser ablation characteristics of hydroxylamine nitrate-based liquid propellants. (August 2022) - Cao, Jinle; Du, Baosheng; Wu, Lizhi; Zhang, Wenhao; Pan, Yue; Ye, Yinghua; Shen, Ruiqi; Zhou, Bin
Abstract: Hydroxylamine nitrate is a nontoxic green energetic propellant that has a high energy density and wide application prospects in the field of aerospace propulsion. Here, the laser ablation and propulsion properties of hydroxylamine nitrate-based propellants doped with aluminum nanoparticles were studied. The results showed a significant improvement in the laser absorption properties of hydroxylamine nitrate doped with aluminum nanoparticles. The maximum absorption rate increased by more than 80%, while the absorption depth decreased considerably with a minimum of 277 μm. The sputtering behavior also weakened during laser ablation, and the impulse of hydroxylamine nitrate could be enhanced by doping aluminum nanoparticles. With the 0.7wt% mass fraction of aluminum nanoparticles, a maximum impulse bit of 57.55 μN·s at 90 mJ laser energy. This is led to a maximum energy conversion efficiency of 218.1% and an enhancement of the kinetic energy of the hydroxylamine nitrate-based propellant of 56% with laser energy of 25 mJ. Compared with ordinary liquid propellants, doped samples have better propulsion performance. Highlights: HAN doped with Al nanoparticles improve the absorption performance of 1064 nm laser. The ablation characteristics were analyzed from the absorption mechanism. The contribution and mechanism of Al nanoparticles to energy conversion were given. The energy conversion mechanism of HAN-based propellant under laser ablation was analyzed.